4u-26=-2(u+7)

Simple and best practice solution for 4u-26=-2(u+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4u-26=-2(u+7) equation:


Simplifying
4u + -26 = -2(u + 7)

Reorder the terms:
-26 + 4u = -2(u + 7)

Reorder the terms:
-26 + 4u = -2(7 + u)
-26 + 4u = (7 * -2 + u * -2)
-26 + 4u = (-14 + -2u)

Solving
-26 + 4u = -14 + -2u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '2u' to each side of the equation.
-26 + 4u + 2u = -14 + -2u + 2u

Combine like terms: 4u + 2u = 6u
-26 + 6u = -14 + -2u + 2u

Combine like terms: -2u + 2u = 0
-26 + 6u = -14 + 0
-26 + 6u = -14

Add '26' to each side of the equation.
-26 + 26 + 6u = -14 + 26

Combine like terms: -26 + 26 = 0
0 + 6u = -14 + 26
6u = -14 + 26

Combine like terms: -14 + 26 = 12
6u = 12

Divide each side by '6'.
u = 2

Simplifying
u = 2

See similar equations:

| -10x-35+24x=6x+13 | | x+x+75+x-15=180 | | X+13x+42= | | 2lnx=ln(x+2) | | 205/x=5.54 | | 5(3x+2)-2=4(4x-3) | | (4/x^2) | | 23x+2y=-19 | | -3(-2x-2)=12 | | 2.6=3a | | 7b-10+69-3=83 | | y-42=180 | | 8(1+5)+5=12+5x | | 1-4lnx=lnx-9 | | 10f+8=11f+7 | | 6(y+1)=2y+18 | | 4m+10=36 | | 23+5x=111-3x | | 7(51)=10 | | -2(3-7)-4= | | x=11+7y | | 2b+b=7 | | 13+3x=3n-29 | | 3y-2=4(2y-3) | | 13+3x=-29-3n | | 2.6=0.2-4 | | -2a+(5a-3)-(3a+4)= | | 8-3k+6k=2k-3 | | -4(x+3)-7=-3x-15 | | 6(w-3)-(2w-5)=3w | | y=-8/9x-8/9 | | -5+7x+7=8(x+3)-9 |

Equations solver categories